(untitled) (PERcursos Linguísticos, 2020)
Pragmatic markers are crucial components of oral discourse, since their misuse or lack thereof at the pragmatic level renders the discourse inappropriate or even rude (BRINTON, 1996, p. 35-36), as demonstrated by research carried out with advanced learners of English (NIKULA, 1996; PIIRAINEN-MARSH, 1995; AUTHOR, YEAR). For that reason, we reflect on the necessity of teaching such expressions to learners of English as a foreign language, and to complete and corroborate our reflection we investigated the markers of oral discourse in dialogues of two English textbooks, and the presence of activities which make their use possible as well, since the textbook is the basis of teachers` actions most times. (AUTHOR, YEAR). Our findings revealed a rich diversity of markers and activities addressing their use. Our theoretical framework is grounded on the research undertaken by Schiffrin (1987), Fraser (2015, 2009, 1999, 1996), Keller (1979), Schorup (1999, 1985), Erman (1992), Östman (1981), Nikula (1996), Brinton (1996) and Jucker (1997). Key words: Pragmatic Markers. Textbook. Teaching and Learning English as a Foreign Language.